2009
DOI: 10.1101/gr.092668.109
|View full text |Cite
|
Sign up to set email alerts
|

The colorectal cancer risk at 18q21 is caused by a novel variant altering SMAD7 expression

Abstract: Recent genome-wide scans for colorectal cancer (CRC) have revealed the SMAD7 (mothers against decapentaplegic homolog 7) gene as a locus associated with a modest, but highly significant increase in CRC risk. To identify the causal basis of the association between 18q21 variation and CRC, we resequenced the 17-kb region of linkage disequilibrium and evaluated all variants in 2532 CRC cases and 2607 controls. A novel C to G single nucleotide polymorphism (SNP) at 44,703,563 bp was maximally associated with CRC r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
1
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 27 publications
(26 reference statements)
5
77
1
4
Order By: Relevance
“…44 For the 8q24.3 locus, allelic imbalance specific for the risk allele was reported, 45 while for the loci on chromosome 8q23.3 (EIF3H) and 18q21 (SMAD7), this association with CRC was not found. 46,47 In our study, no evidence for allele specific imbalance was found for the SNPs that increase the risk of CRC.…”
Section: Cancer Geneticscontrasting
confidence: 78%
“…44 For the 8q24.3 locus, allelic imbalance specific for the risk allele was reported, 45 while for the loci on chromosome 8q23.3 (EIF3H) and 18q21 (SMAD7), this association with CRC was not found. 46,47 In our study, no evidence for allele specific imbalance was found for the SNPs that increase the risk of CRC.…”
Section: Cancer Geneticscontrasting
confidence: 78%
“…green fl uorecent protein (GFP) 42 . Transgenesis was performed using the I-SceI method following the protocol already described 43 .…”
Section: Methodsmentioning
confidence: 99%
“…A possible mechanism of action is thought to be via the influence of these SNPs on distal enhancer elements that regulate the expression of critical target genes (9)(10)(11)(12). Evidence exists for regulatory activity of SNPs located in several regions, including 8q24, 8q21, and 17q24 (13,14).…”
Section: Role Of Gwas Snps In Gene Regulationmentioning
confidence: 99%